ANALISIS KONSEP, IMPLEMENTASI, DAN DAMPAK PENDIDIKAN NILAI DALAM KURIKULUM NASIONAL: SEBUAH STUDI KEPUSTAKAAN - Ani Khasbiyah; Dewi Apriyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
National education currently faces complex challenges in the globalization era, where technological advancements often outpace the emotional and moral maturity of the younger generation. The phenomenon of character degradation and the erosion of cultural identity necessitates a reinforcement of value education, which is frequently sidelined by purely academic targets. This study aims to deeply analyze the concept, implementation strategies, and impact of value education within the Indonesian national curriculum, as well as conduct a comparative study with education systems in developed countries. Employing a qualitative approach with a library research method, this study examines literature related to educational policies, pedagogical theories, and global practices. The results indicate that the implementation of value education in Indonesia does not stand alone but is integrated through the synergy of the